Sub-project 3: fish trade, processing and marketing (Denmark, 1996)
The contents of the raw material report give an overview of the development, describe and asses the present situation of the marine capture fisheries and aquaculture sector and suggest ways for further development.
Keywords: Fishery management,Aquaculture; Economic aspects